2021
DOI: 10.1016/j.dcn.2021.100957
|View full text |Cite
|
Sign up to set email alerts
|

Rich-club structure contributes to individual variance of reading skills via feeder connections in children with reading disabilities

Abstract: The present work considers how connectome-wide differences in brain organization might distinguish good and poor readers. The connectome comprises a ‘rich-club’ organization in which a small number of hub regions play a focal role in assisting global communication across the whole brain. Prior work indicates that this rich-club structure is associated with typical and impaired cognitive function although no work so far has examined how this relates to skilled reading or its disorders. Here we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 95 publications
(139 reference statements)
1
10
0
Order By: Relevance
“…Structural connectivity in individual white matter pathways is associated with pre-reading skills in young children ( Saygin et al, 2013 , Walton et al, 2018 , Wang et al, 2021 ); our findings show that the organization of the reading network is also associated with phonological awareness. Our findings are in good agreement with previous studies in school-aged children showing higher structural network efficiency associated with better reading and academic performance ( Bathelt et al, 2018 , Lou et al, 2021 ). This also adds to previous findings in an overlapping sample showing better pre-reading abilities to be associated with stronger functional connectivity ( Benischek et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Structural connectivity in individual white matter pathways is associated with pre-reading skills in young children ( Saygin et al, 2013 , Walton et al, 2018 , Wang et al, 2021 ); our findings show that the organization of the reading network is also associated with phonological awareness. Our findings are in good agreement with previous studies in school-aged children showing higher structural network efficiency associated with better reading and academic performance ( Bathelt et al, 2018 , Lou et al, 2021 ). This also adds to previous findings in an overlapping sample showing better pre-reading abilities to be associated with stronger functional connectivity ( Benischek et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…In school-aged children, Lou et al (2021) found the structural connectivity strength between central and peripheral nodes in the structural connectome of reading regions (e.g., inferior frontal and occipital, middle and superior temporal, supramarginal, precentral, and Heschl’s gyri) was associated with reading efficiency and phonemic decoding, while local efficiency was associated with phonemic decoding. They also found no associations of RAN with any graph theory measures ( Lou et al, 2021 ). Another study in school-aged children found stronger academic performance associated with overall better organization of the white matter connectome ( Bathelt et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, alteration in rich-club connections reflects the brain's global communications impairment (Stam, 2014;van den Heuvel & Sporns, 2011). Abnormalities in rich (i.e., hub-hub), feeder (i.e, hubnonhub), and local (i.e., nonhub-nonhub) connections have been reported previously in individuals with neurological disorders along with alteration in local topological metrics (Cui et al, 2022;Lou et al, 2021;Ray et al, 2014;Shu et al, 2018;B. Wang et al, 2021;Y.…”
Section: Rich-club Organization Is Intact In Apdmentioning
confidence: 69%
“…The rich-club topology can provide important information for integrated communication in brain networks (Colizza et al, 2006; van den Heuvel & Sporns, 2011). Consequently, studying the topological architecture of a rich-club organization could uncover pathological bases for brain diseases (Daianu et al, 2015, 2014; Liu et al, 2021; Lu et al, 2021; Shu et al, 2018; Van Den Heuvel et al, 2013; Xue et al, 2020) and disorders (Cui et al, 2022; Keown et al, 2017; Lou et al, 2021; Ray et al, 2014; B. Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The pre-reader studies were done mainly in the United States with English language speakers (50%) [16][17][18]22], followed by 40% [20,21,23] in Belgium with Dutch speakers, and 10% [19] in Germany with German speakers, including young children under 6 years old male and females and balanced distribution (a total of 193 females to 215 males) and with a sample variation of 10 to 46 children in each comparison group. In studies with reading-stage children, 47% spoke Englishfrom the USA (45%) [25,27,[31][32][33]39,42,44,48,50,[52][53][54]56] and Canada (2%) [28,29]; 17% spoke French (the study was carried out in France [26,30,34,38,45]); 11% spoke Dutch-the studies were carried out in Belgium and Netherlands [37,41]; 8% were German; 6% spoke Mandarin-the studies were carried out in China [43] and Taiwan [36]; and 3% of studies were done with speakers of Arabic (Egypt) [35], Spanish (from Spain) [47], Portuguese (from Brazil) [49], or Italian (from Italy) [51]. In adults, the language of studies was less varied: 38% spoke English, and the studies were carried out in New Zealand [59] and the USA [62,64]; 25% spoke German (Ge...…”
Section: Demographic and Neuropsychological Characteristics Of Studie...mentioning
confidence: 99%